Who are the Responsible for the Results of the Evaluations ?: Towards a Value Added Approach in Education - F. Javier Murillo Torrecilla (Universidad Autónoma de Madrid, 2016)
Never in history as in recent years, schools have been so pressured to demonstrate high results in student learning through their performance on standardized tests. The proliferation of external evaluations that are currently experienced, of all types and origins, focused on measuring the academic achievement of students in certain curricular areas leads to, in many cases, schools and their teachers being held accountable for the results obtained, results that are always labeled improvable.